(untitled) (Journal of Economic Research & Business Administration, 2018)
Globalization and the post-industrial era require entities to use new methods to reduce production costs. At this stage of development, outsourcing is becoming more and more popular for the workforce dispatching. The advantage of agency work lies in its flexibility. Against the backdrop of the agency work positive aspects, there are difficulties for both employers and workers causing disagreements arising from ineffective relations between market participants due to enforcement (mainly in countries with transition economies) and poor labor relations regulation. These circumstances cause a conflict of interest illustrating social injustice. The purpose of the article is to study the peculiarities of outsourcing in the labor legislation sphere on the developed countries example. To study the legal framework of agency work in Kazakhstan. Identify the problems of the emergence of outsourcing as a type of agency work. This article presents foreign experience in the development of agency labor in Germany, the United States of America, Great Britain and Japan, where a comparative approach has been applied to the study of agency work in developed countries. The issues of agency work formation and regulation are covered in these countries. The issues of agency work formation in Kazakhstan, in particular, employment agencies, were also studied. The civil law base serves as a foundation for studying agency work, outsourcing in particular. For the convenience of studying the agency work, a comparative approach is used in the agency work sphere, which reflects positive and negative aspects of outsourcing as a kind of agency work. The importance of the article is to systematize the agency work formation issues in Kazakhstan in the legal sphere, where indirect methods of regulation are reflected. The experience of reforming shows that in developed countries, the government should establish more flexible outsourcing rules that can ensure fairness for all players in the agency work market.